The effect of plasma nitriding duration on the tribological performance of Ni-B-Gr self-lubricant composite coatings on AISI 4140 steel - Vahid Niksefat; Farzad Mahboubi (Journal of Materials Research and Technology)
This study investigates the tribological characteristics of Nickel-Boron-Graphite (Ni-B-Gr) self-lubricating composites, focusing on the impact of plasma nitriding duration on wear resistance in AISI 4140 steel. The research aims to improve the durability and efficiency of these coatings under sliding wear conditions. The Ni-B-Gr composites were applied to AISI 4140 steel using an electroless method, with the Ni-B matrix providing structural rigidity and graphite flakes (<20 μm, 0.275 g/L) acting as a self-lubricating agent. Plasma nitriding (PN) treatment was performed at 400 °C for 30–240 min, using a gas combination of 25% nitrogen and 75% hydrogen. The Ni-B-Gr coatings were characterized using various techniques, including X-ray diffraction, field emission scanning electron microscopy, inductively coupled plasma optical emission spectroscopy, microhardness testing, and tribological assessments. The surface roughness analysis revealed that initial plasma nitriding increased surface roughness due to sputtering and redeposition effects. However, longer nitriding durations leveled surface peaks and valleys, optimizing roughness for improved tribological performance. The Ni-B-Gr composite treated with plasma nitriding for 60 min showed a 75% reduction in specific wear rate and a 30% decrease in coefficient of friction compared to untreated Ni-B-Gr coatings. Notably, bearing area curves demonstrated that the PN Ni-B-Gr composite treated for 60 min extended the wear lifespan by 1.5 times compared to the untreated Ni-B-Gr composite. This study showcases the promising tribological performance of the coatings for gear applications. Plasma nitriding significantly mitigated adhesive, abrasive, and oxidative wear mechanisms, enhancing the coating's resistance to high-stress conditions in gear applications.